1989
DOI: 10.1002/pros.2990150213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pubertal development on estrogen receptor levels and stromal morphology in the guinea pig prostate

Abstract: Using an immunocytochemical assay (ERICA) with a monoclonal antibody (H222Sp gamma) to the human estrogen receptor, we have demonstrated a stromal localization of the estrogen receptor in the dorsolateral prostate of the guinea pig. Specific staining of estrogen receptor in the guinea pig prostate was confined to the nuclei of periacinar and interacinar stromal cells. In comparison with prepubertal tissues, estrogen receptor staining intensity was markedly reduced in postpubertal prostatic tissues. No immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
1
7
0
2
Order By: Relevance
“…It clear that the change in the pattern of collagen budding with reduction in relative proportion of stroma compartment caused by gestational BPA exposure resulted in changes in the distribution and aggregation of extracellular matrix elements (Brandt et al, 2014). Previous reports have shown that exposure to estradiol may increase the synthesis of collagen in the stromal cells and make collagen bundles thicker in rodent prostate (Tilley et al, 1989;Prins et al, 2007;Scarano et al, 2005Scarano et al, , 2008. However, serum levels of estradiol on PND21 did not differ among the experimental group but some toxicological studies in which EDs were administered during pregnancy showed that hormone levels tend to normalize after exposure; however, the tissue-specific effects remain (Putz et al, 2001;Scarano et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…It clear that the change in the pattern of collagen budding with reduction in relative proportion of stroma compartment caused by gestational BPA exposure resulted in changes in the distribution and aggregation of extracellular matrix elements (Brandt et al, 2014). Previous reports have shown that exposure to estradiol may increase the synthesis of collagen in the stromal cells and make collagen bundles thicker in rodent prostate (Tilley et al, 1989;Prins et al, 2007;Scarano et al, 2005Scarano et al, , 2008. However, serum levels of estradiol on PND21 did not differ among the experimental group but some toxicological studies in which EDs were administered during pregnancy showed that hormone levels tend to normalize after exposure; however, the tissue-specific effects remain (Putz et al, 2001;Scarano et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…only a portion of the cells are ERα positive while many remain ERα negative. Studies in rodent prostate glands have shown a relatively high percentage of stromal cells express ERα mRNA and protein during perinatal morphogenesis and this proportion significantly declines thereafter suggesting a specific role for ERα in prostate development [73,75,76]. A decline in expression with puberty suggests that androgens may normally suppress ERα expression, a finding that has been borne out in direct studies [77,78].…”
Section: Erαmentioning
confidence: 99%
“…Since AR are induced in rat prostate epithelium by postnatal day 1-3, it is possible that androgen-driven epithelial signals also contribute to morphogenesis and differentiation of the prostate (15) The developing prostate gland also expresses other members of the steroid receptor superfamily including estrogen receptors ERα and ERβ and retinoic acid receptors RARα, β and γ which are liganded by all-trans or 9-cis retinoic acid as well as RXR α, β and γ which are activated by 9-cis retinoic acid alone. Studies in rodent prostate glands have shown relatively high stromal cell ERα expression during perinatal morphogenesis of the gland which significantly declines thereafter suggesting a specific role for ERα in prostate development (16,18,19). In the rat and murine prostate, ERβ is primarily localized to differentiated luminal epithelial cells (20)(21)(22).…”
Section: Prostate Gland Developmentmentioning
confidence: 99%